"Mission impossible": exploring the viability of power-sharing as a conflict-resolution tool in Syria. Issue 1 (8th February 2016) - Groarke, Emer
Abstract : Purpose: – This paper aims to show the viability of consociational power-sharing as a conflict-resolution tool in Syria. It further argues that a subsequent movement from consociational to centripetal power-sharing is vital to ensure sustainable peace. Design/methodology/approach: – A theoretical overview of power-sharing as a conflict-resolution tool provides the basis for this paper, supported by empirical evidence and qualitative research analysis for its proposed application in Syria. Perceived obstacles to a negotiated settlement are outlined, with suggestions made as to how these issues can be transformed into incentives for invested parties. Such obstacles include Bashar al-Assad remaining in power, and calls for the implementation of Shari'a law by some opposition groups. Findings: – While previously the conditions of the conflict were not conducive to peace talks, this paper finds that regional developments, including the rise of the Islamic State of Iraq and Syria, have re-opened the possibility of, and indeed the necessity for, political negotiations. Detailing the complexity of a conflict that goes far beyond a mere sectarian divide, the findings of this paper dispel the notion that a sectarian partition is a viable model for Syria. The paper highlights the multiple cleavages occurring simultaneously, and shows how a power-sharing model is best suited to deal with them. Originality/value: – The paper analyses the ongoing inertia of political negotiations to peacefully resolve the conflict. It offers an approach to conflict-resolution in Syria that has, thus far, not been adequately considered in academic – or political – spheres.